ANALISIS KINERJA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN BENGKULU TENGAH PERIODE 2019-2024 - Alexsander; Hartini, Septi; Dodo Sutardi (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
The aim of this research is to analyze the performance of the Central Bengkulu Regency DRPD. The method used in this research is a quantitative research method using interview, observation and interview techniques as data collection. After the data is collected, it is then analyzed using qualitative analysis techniques by interpreting it in simple sentences so that conclusions can be drawn as a result of the research. The results of the research show that the 3 indicators, namely Responsiveness, Responsibility and Accountability, which are used to measure the performance of the Bengkulu Regency DPRD in terms of responsiveness, are optimal. In terms of responsibility, accountability is still less than optimal. By using these 3 indicators, it can be said that the performance of the Central Bengkulu Regency DPRD for the 2019–2024 period has not been optimal, so it is felt that evaluation is needed to improve the performance of the Central Bengkulu Regency DPRD.